Novel data support validity of Phoxinus chrysoprasius (Pallas, 1814) (Actinopterygii, Leuciscidae) - Bogutskaya, Nina G.; Diripasko, Oleg A.; Palandačić, Anja (European Journal of Taxonomy, 2023)
The common minnow species Cyprinus chrysoprasius, previously synonymised to Phoxinus phoxinus, was originally described from the Crimean Peninsula (Black Sea – Sea of Azov basin). A genetic analysis of the mitochondrial cytochrome oxydase 1 in the context of a phylogenetic study of European Phoxinus showed that it represents a distinct genetic clade and potentially a valid species. In the present study, we approach the issue following a broader, both genetic and morphological, study in order to check and support the validity of native Crimean Phoxinus under the earliest available name of the species: P. chrysoprasius. Our data demonstrate a reliable genetic distance of this minnow from geographically neighbouring clades and species, and a certain morphological distinctiveness. In order to determine the taxonomic concept of P. chrysoprasius, as a species involved in a genetically well-differentiated, but phenotypically poorly structured complex of east-European Phoxinus, a neotype for the species, based on topotypical material, is herein described and designated. The original type locality of the species is also clarified.